Small Bowel Obstruction from Internal Hernia as a Complicaton of Colonscopy - Robert Patterson; Gerhard Klassen (Canadian Journal of Gastroenterology)
After colonoscopy with polypectomy, a patient developed a surgically acute abdomen. Although abdominal radiology did not show free air, a presumptive diagnosis of bowel perforation was made and laparotomy performed. At the time of surgery the colon was normal, and there was no peritoneal contamination. A loop of ileum was discovered incarcerated into an internal paracecal hernia. The bowel was freed, and the operation was completed without need for resection. Several cases of incarcerated inguinal hernia resulting from endoscopy are described in the medical literature; this is the first reported case of an incarcerated internal hernia as a complication of colonoscopy.